Natural Product Tsunami - Abdolali Mohagheghzadeh (Shiraz University of Medical Sciences, 2016)
Global rising trends for natural products consumption, establishing traditional medicines, vast propagation, and simple access to legal or illegal natural medications have encountered health systems with a disastrous tsunami, which was not fully predicted and programmed for throughout medical education.